MANAJEMEN PENGHIMPUNAN DANA UNTUK EFEKTIVITAS OPERASIONAL LEMBAGA KEUANGAN SYARIAH - aulia, irfa (Moneta: Jurnal Manajemen & Keuangan Syariah, 2025)
Fundraising is a crucial aspect in the operation of Islamic Financial Institutions (IFIs) because it determines the sustainability of their intermediation function and the effectiveness of their performance. This study aims to analyze fundraising management strategies throught four main focuses increasing Third Party Funds (TPF), managing and investing, market segmentation and product promotion, and evaluating fundraising effectiveness. The research method used is a literature study analyzing the result of previous research on Islamic bank in Indonesia. The study results indicate that TPF is the primary source of funds for Islamic financial institutions, therefore,fundraising strategies need to focus on marketing, promotion, Islamic financial literacy education, and contract based product innovation. Invesment fund management requirest compliance with sharia principles, tranparency, prudence, and social responsibility to provide halal result and social benefits. Market segmentation and product promotion play a role in expanding the customer base and strengthening the institution can be conducted through financial indicators such as the Financing Deopsit Ratio (FDR) to assess the optimization of fund distribution. Thus, effective fundraising management in IFIs not only creates financial success but also reflects a commitment to justice, welfare, and Sharia based economic development.